A population study using the human erythrocyte PIG‐A assay. (1st September 2016) - Cao, Yiyi; Yang, Li; Feng, Nannan; Shi, Oumin; Xi, Jing; You, Xinyue; Yin, Chunrong; Yang, Huan; Horibata, Katsuyoshi; Honma, Masamitsu; Qian, Biyun; Weng, Wei; et al.
Abstract : Erythrocyte‐based PIG‐A assay is sensitive and reliable in detecting exposure to mutagenetic agents in animal studies, but there are few data from human populations. In this study, we employed a method for detecting CD59 phenotypic variants, resulting from mutation in the PIG‐A gene, in human red blood cells (RBCs), and determined the CD59‐deficient RBC (RBC CD59− ) frequencies in 217 subjects from general population. The majority of subjects had a relatively low mutant frequencies (MFs) (average, 5.25 ± 3.6 × 10 −6, median, 4.38 × 10 −6, for all subjects), but with males having a significantly greater MFs (5.97 ± 4.0 × 10 −6 ) than females (4.19 ± 2.5 ×10 −6 ). There was no correlation between MFs and age. In addition, MFs showed no difference between smoker and nonsmoker, and also no association with smoke duration in male subjects. However, there was a significant correlation between cigarette‐pack‐years which indicated that the MF was only slightly elevated with the increase of cigarette‐pack‐years. Moreover, intraindividual variations were investigated in three volunteer subjects over 300 days, and the MFs were relatively stable and repeatable. Furthermore, a pilot study by using white blood cell (WBC) assay based on labeling with FLAER was performed in volunteer subjects. The MFs of FLAER‐deficient WBC (WBC FLAER− ) and RBC CD59− were consistently elevated in two subjects. Our findings provide baseline data that will be helpful in designing further studies using the PIG‐A assay to monitor the genotoxic effects of carcinogens in human populations. Environ. Mol. Mutagen. 57:589–604, 2016. © 2016 Wiley Periodicals, Inc.